Genetic variability and breeding potential of Flintisa Composite of maize in two levels of technology - Costa Andrade, Joao Antonio da [UNESP] (Brazilian Soc Plant Breeding, 2019)
The purpose this study was to verify the breeding potential of Flintisa Composite for low (LT) and high (HT) technology of cultivation, and the best selection strategy to be adopted. For this reason half-sib progenies were evaluated in the two technological levels. In HT, it was used basic fertilization, two top dressing and supplementary irrigation. In LT, these practices were suppressed, and less fertile soil was used. Except for grain yield (GY), heritability was high at plant level and at progenies mean level. With mass selection, estimated gains ranged from 3.3% (GY in LT) to 41.8% (tassel branches number in LT). For half-sib selection, estimated gains ranged from 4.7% (plant height in HT) to 23.6% (erect plants in HT). For ear height, stratified mass selection in just one environment should be valid for both. Half-sib selection, with S-1 recombination should be adopted in specific selection programs for LT and HT.
Keywords: heritability; genetic additive variance; selection; genotype x environment interaction